2018
DOI: 10.1016/j.ejpb.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of polymersomes loaded with 225Ac evaluated in 2D and 3D in vitro glioma models

Abstract: Alpha emitters have great potential in targeted tumour therapy, especially in destroying micrometastases, due to their high linear energy transfer (LET). To prevent toxicity caused by recoiled daughter atoms in healthy tissue, alpha emitters like Ac can be encapsulated in polymeric nanocarriers (polymersomes), which are capable of retaining the daughter atoms to a large degree. In the translation to a (pre-)clinical setting, it is essential to evaluate their therapeutic potential. As multicellular tumour spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…However, the analysis presented here could function as a prerequisite for the interpretation of 2-D experiments for comparison to 3-D in vitro systems, where radiation from neighbouring cells is much higher [21]. In addition, in current experimental set-up, the small amount of PMs translates to a small amount of alpha particles that are being emitted and a low delivered dose to cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the analysis presented here could function as a prerequisite for the interpretation of 2-D experiments for comparison to 3-D in vitro systems, where radiation from neighbouring cells is much higher [21]. In addition, in current experimental set-up, the small amount of PMs translates to a small amount of alpha particles that are being emitted and a low delivered dose to cells.…”
Section: Discussionmentioning
confidence: 99%
“…225 Ac, for example, has multiple alpha emissions in its decay chain. The use of 225 Ac has seen therapeutic potential in glioma models [21]. For future studies, the use of 225 Ac might be more relevant to investigate the benefit of geographically fixing radiolabeled PMs intracellularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough understanding of the cellular distribution of the nanocarriers and interactions with cellular structures is a key issue in drug carrier systems due to the direct correlation that exists between cellular uptake, intracellular trafficking mechanism, and drug bioavailability, clinical efficacy, and therapeutic outcome of the entrapped therapeutic compound [17]. In a previous study, we reported on the kinetics of the uptake of fluorescently labeled polymersomes in U87 spheroids [16]. In about 4 days, the polymersomes have diffused nearly throughout the spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 h incubation, the free FITC was removed by passing the solution through a PD10 column. For details regarding the polymersomes, see De Kruijff et al [16].…”
Section: Polymersome Formation and Drug Loadingmentioning
confidence: 99%